2004
DOI: 10.1007/s00330-003-2217-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in computed tomography features following preoperative chemotherapy for nephroblastoma: relation to histopathological classification

Abstract: The objective of this study is to assess computed tomography (CT) changes, both volume estimates and subjective features, following preoperative chemotherapy for nephroblastoma (Wilms' tumour) in patients treated on the United Kingdom Children's Cancer Study Group Wilms' Tumour Study-3 (UKW-3) protocol and to compare CT changes and histopathological classification. Twenty-one nephroblastomas in 15 patients treated on UKW-3 were included. All patients were examined by CT before and after preoperative chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…As indicated in previous studies, our findings suggest a correlation between ADC distribution and biological response to chemotherapy (12,13,(17)(18)(19)(20)(21). Previous studies have shown that tumor shrinkage might be a delayed or insensitive marker (in case of partial response) to evaluate chemotherapy response; absence of reduction in tumor size does not necessarily mean no response (13,14,22). Particularly for solid, viable tumors, new methods are needed to histopathologically detect a lack of chemotherapy response in a shrinking tumor or the degree of response in a growing tumor.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…As indicated in previous studies, our findings suggest a correlation between ADC distribution and biological response to chemotherapy (12,13,(17)(18)(19)(20)(21). Previous studies have shown that tumor shrinkage might be a delayed or insensitive marker (in case of partial response) to evaluate chemotherapy response; absence of reduction in tumor size does not necessarily mean no response (13,14,22). Particularly for solid, viable tumors, new methods are needed to histopathologically detect a lack of chemotherapy response in a shrinking tumor or the degree of response in a growing tumor.…”
Section: Discussionsupporting
confidence: 76%
“…The ADC values of malignant masses are relatively lower than those of benign masses, although overlapping ADC values of malignant and benign lesions have also been reported (1, 6-12). Currently, in children the assessment of solid tumors' response to chemotherapy is based on size reduction; but this method can be unreliable as a marker, as tumors that shrink substantially may still be composed mainly of malignant cells (13,14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, such methods were utilized to confirm the presence of a mass, suggesting a specific diagnosis, but later they started playing a role in the therapy and surgical plannings, besides the evaluation of the treatment response (2,(5)(6)(7)(8) . Certain imaging findings such as presence of metastases or vascular invasion have contributed to the therapeutic planning.…”
Section: Discussionmentioning
confidence: 99%